2012
DOI: 10.1017/s0266267112000272
|View full text |Cite
|
Sign up to set email alerts
|

Adam Smith and the Modern Science of Ethics

Abstract: Third-party decision-makers, orspectators, have emerged as a useful empirical tool in modern social science research on moral motivation. Spectators of a sort also serve a central role in Adam Smith's moral theory. This paper compares these two types of spectatorship with respect to their goals, methodologies, visions of human nature and emphasis on moral rules. I find important similarities and differences and conclude that this comparison suggests significant opportunities for philosophical ethics to inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…6 A classic example is Lerner (1982), which discusses how people tend to believe in a just world, even in the presence of contradictory evidence. 7 In economics, the possibility of self-serving biases goes back to Adam Smith (Konow 2012). More recently, several studies have demonstrated the presence of self-serving bias and its economic significance.…”
Section: B Relation To Previous Workmentioning
confidence: 99%
“…6 A classic example is Lerner (1982), which discusses how people tend to believe in a just world, even in the presence of contradictory evidence. 7 In economics, the possibility of self-serving biases goes back to Adam Smith (Konow 2012). More recently, several studies have demonstrated the presence of self-serving bias and its economic significance.…”
Section: B Relation To Previous Workmentioning
confidence: 99%
“…subjects whose decisions on the criteria for allocating resources directly affect their own payoff) decide differently from "spectators" (i.e. subjects who choose a distributive criterion that affects payoff of other players) (Konow, 2011) and that the 1 Strict egalitarianism implies the absence of any kind of inequality in wealth distribution even when people contribute in different ways to wealth creation. 2 Libertarianism establishes that individuals should be considered totally responsible for their contributions in producing wealth (whatever their merit in achieving them) and a fair distribution should precisely reflect the different contributions.…”
Section: Introductionmentioning
confidence: 99%
“…We imagine ourselves being seen by someone else, unrelated to us, and our conduct being judged impartially by this spectator. James Konow (2012) But the process of moral development is not automatic because our perception of ourselves and our surrounding may be biased by our limited vision. We need to learn how to perceive moral and physical distances alike.…”
Section: "Think For Yourself" Science Of Man-history and The Labmentioning
confidence: 99%
“…James Konow (2000) suggests Smith's estimate might be conservative: even under sterile laboratory conditions, which are least conducive to self-deception, almost two-thirds of unfairness has been traced to such a bias (in Konow 2012). The problem may be exacerbated, as Warren Samuels (2007) implies, by our desire to "allay [the] tumult of the imagination" caused by events which we cannot explain: we "smooth the imagination" with connections (beliefs), independently of their truth (see also: Schliesser 2013).…”
Section: "Think For Yourself" Science Of Man-history and The Labmentioning
confidence: 99%